213 Effects of Different Levels of Hemeprotein Supplementation on Performance and Blood Physicochemical Parameters in Weaned Piglets. (10th April 2018) - Yu, L; Liu, H; Wang, J; Jiang, G; Cheng, G
Abstract: This experiment was conducted to investigate effects of different levels of hemeprotein (158S) supplementation on performance and blood physicochemical parameters in weaned piglets, and to determine the optimal level of hemeprotein (158S) supplementation in weaned piglet diet. A total of 192 weaned Duroc × Large White × Landrace piglets at 42 d of age (initial BW 10.49 ± 0.06 kg) were selected and were randomly divided into four groups receiving diets containing 0 (control group), 700 (158S700 group), 900 (158S900 group) and 1200 (158S1200 group) mg/kg 158S respectively (4 replicates per group and 12 piglets per replicate). The experiment lasted for 31 d, including 3 d of adaption and 28 d of official trial. All data was analyzed as a randomized complete block design using GLM of SAS (SAS Inst., Inc. Cary, N.C). The results indicated that ADG in the 158S900 group in the first 14 d (372.24 g/d) was higher than 0、700 and 1200 groups (304.05, 314.40, and 314.52 g/d, respectively) ( P < 0.05), and the F/G in the 158S900 group (1.62) was lower than 0、700 and 1200 groups (1.91, 1.87, and 1.78, respectively) ( P < 0.05), however, ADG in the 158S700 group was greater than the control group in the last 14 d (512.46 vs 427.90 g/d, P = 0.011), but was not different with the 158S900 group (466.22 g/d, P = 0.126). The blood hemoglobin (HGB) in the 158S900 group (111.67 g/L) rose more than 0、700 and 1200 groups (98.50, 100.75, and 99.88 g/L, respectively, p=0.046) and the hematocit (HCT) was higher than the control group in the 14 th d (33.00% vs 29.00%, P = 0.029). While in the 28 th d, the HGB in the 158S900 group was greater than the control group (105.22% vs 98.04%) ( P= 0.032). Also, as the 158S supplementation in the diets increased, ferritin (Fn) in the serum in the 14 th d was tend to rise ( P = 0.067), and Fn in the 158S900 group and 158S1200 group were higher than the control group ( P = 0.035 and 0.017, respectively). In conclusion, supplementation of hemeprotein (158S) to the diet can improve the performance and the iron status of weaned piglets, and the optimal supplementation level is 700-900 mg/kg, which is dependent on the weaning age and the iron status of piglets.